Value-creating factors in customer and supplier relationships in the light of corporate competitiveness - Wimmer, Agnes; Csesznák, Anita (Vezetéstudomány / Budapest Management Review, 2023)
Business (customer and supplier) relationships can create or destroy value. Recognition of the value-creating potential of relationships and the ability to manage them, as well as the managers’ attitudes and approach in this regard, can become important success factors. In this study, the authors compare the approaches of managers in competitive and less competitive companies based on the results of the latest questionnaire survey conducted by the Competitiveness Research Centre of Corvinus University of Budapest. Their analysis indicates that competitive companies are more open with their business partners and pay more attention to supplier relations. In addition to the classic expectations (such as service quality, costs), they place a high value on longer-term values, reliability, expertise and learning opportunities in the relationship, and, overall, they tend to view business relationships as a more value-creating factor than less competitive companies.